The Role of Emotional Eating A Mediator in Relationship between Sleep Duration and Quality with Carbohydrate Intake among Pregnant Women - Agrisdian, Zerly; Probandari, Ari; Pamungkasari, Eti (Universitas Airlangga, 2022)
Carbohydrate is one of the nutrients that is needed during pregnancy. Increased demand during pregnancy causes pregnant women to consume carbohydrates in excess, which occurs due to emotional eating. The increment of emotional eating is assumed to be triggered by insufficient sleep duration and poor sleep quality. This study was aimed to investigate the role of emotional eating as mediator in relationship between sleep duration and quality with carbohydrate intake among pregnant women. This study applied an analytic survey with cross-sectional design on 105 pregnant women in the second and third trimesters at Bondowoso District were sampled through multistage random sampling technique. In this study, the exogenous variables were sleep duration and quality. Meanwhile, the endogenous variables were carbohydrate intake. Emotional eating was the mediator. Data were collected using the Emotional Eater Questionnaire (EEQ), Pittsburgh Sleep Quality Index (PSQI), and 3í—24 hours food recall. Data were analyzed using path analysis. There was a direct relationship between duration and quality of sleep with emotional eating (P <0.001 dan 0.002). Sleep duration and quality were not directly associated to carbohydrate intake (P 0.817 dan 0.z724). A direct relationship was shown by emotional eating and carbohydrate intake variables (P<0.001). It is concluded that emotional eating plays a role in the indirect relationship between sleep duration and quality with carbohydrate intake for pregnant women in the second and third trimesters. Pregnant women should be able to regulate sleep patterns and dietary intake.